Structural chemistry and magnetic properties of Y₂CoGe₄O₁₂ - Liu, X; Battle, P; Ridout, J; Xu, D; Ramos, S (Elsevier, 2015)
Polycrystalline Y₂CoGe₄O₁₂ has been prepared by standard ceramic methods. The crystal structure (space group P4/nbm; a=9.8465(2), c=4.92986(9) Å) consists of metal-rich layers separated from each other by Ge4O12 groups comprised of four corner-sharing GeO4 tetrahedra. Two cation sites lie within the layers; an eight-coordinate site occupied by yttrium and a six-coordinate site occupied by a 1:1 disordered distribution of yttrium and cobalt. Neutron diffraction revealed two-fold disorder on the oxide sublattice; this has been elucidated using Co K-edge EXAFS spectroscopy. The availability of two sites allows each oxide ion to accommodate the coordination preferences of its single Co/Y neighbour; the GeO4 tetrahedra distort to absorb any consequent strain. The octahedron of anions around each Co2+ cation shows a pseudo-tetragonal distortion with a strain (Co–O)eq–(Co–O)ax/(Co–O)eq=−0.173. This results in an unusually large effective magnetic moment of 6.05 µB per Co2+ cation.